2022
DOI: 10.1136/oemed-2021-108053
|View full text |Cite
|
Sign up to set email alerts
|

Occupational noise exposure and risk of incident stroke: a pooled study of five Scandinavian cohorts

Abstract: ObjectivesTo investigate the association between occupational noise exposure and stroke incidence in a pooled study of five Scandinavian cohorts (NordSOUND).MethodsWe pooled and harmonised data from five Scandinavian cohorts resulting in 78 389 participants. We obtained job data from national registries or questionnaires and recoded these to match a job-exposure matrix developed in Sweden, which specified the annual average daily noise exposure in five exposure classes (LAeq8h): <70, 70–74, 75–79, 80–84, ≥8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The presented JEMs have already been used in several studies ( Eriksson et al 2018 ; Enoksson Wallas et al , 2019 ; Wallas et al 2018 , 2019 , 2020 ; Aarhus et al 2020 ; Eriksson et al 2021 ; Lissaker et al 2021 ; Thacher et al 2022 ) to study health effects from noise exposure such as cortisol levels, asthma, birth outcomes, and cardiovascular disease. We anticipate further use as an increasing number of epidemiological studies has shown health effects as a result of long-term exposure to noise ( An et al 2018 ; Kerns et al 2018 ; Brauner et al 2019 ; Liu et al 2022 ; Wei et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The presented JEMs have already been used in several studies ( Eriksson et al 2018 ; Enoksson Wallas et al , 2019 ; Wallas et al 2018 , 2019 , 2020 ; Aarhus et al 2020 ; Eriksson et al 2021 ; Lissaker et al 2021 ; Thacher et al 2022 ) to study health effects from noise exposure such as cortisol levels, asthma, birth outcomes, and cardiovascular disease. We anticipate further use as an increasing number of epidemiological studies has shown health effects as a result of long-term exposure to noise ( An et al 2018 ; Kerns et al 2018 ; Brauner et al 2019 ; Liu et al 2022 ; Wei et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%